Perception of Professional Engineers toward Quality of Worklife and Organizational Commitment: A Case Study - Zin, Razali Mat (Gadjah Mada International Journal of Business, 2004)
This empirical investigation was aimed to determine the pattern of theÂ  relationships between the perceived presence of quality of worklife (QWL) factors and organizational commitment using samples from professional engineers in Malaysia. Engineers in private sector were selected to participate in this study. A total of 250 sets of questionnaires were sent to the selected organizations, and 152 useable questionnaire representing a response rate of 60.8% were used for statistical analysis. A QWL measure consisting of seven factors: growth and development, participation, physical environment, supervision, pay and benefit, social relevance, and workplace integration was developed based on Waltonâs (1974) conception. The three-component model and measure of organizational commitment developed by Allen and Meyer (1990) was adopted in this study. Results of regression analysis indicated that only two QWL factors, growth and development and pay and benefit, were significant in explaining organizational commitment. Implication and suggestions for further research are also discussed.